Technical Guidance for Revitalizing Land Yard In the Family Welfare Empowerment Group (PKK) Pasir Mulya Village, Bogor City - Masnang, Andi; Jannah, Asmanur; Yuliana Purba, Tembaten; Rosyad, Astryani (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
Counseling and training on verticulture-based land optimization to revitalize narrow land yards for PKK groups and housewives aim to increase the ability of PKK groups in the field of verticulture-based cultivation technology. It is hoped that after this activity, they will be able to optimize themselves and their land, and there will be an increase in the income and welfare of the PKK group and housewives. The approach method used in this activity is conducting counselling and training. This activity consists of three stages, namely counseling, training in making planting media, and training in how to plant. The results of the activity showed that the participants of this activity stated that their knowledge of the technique of revitalizing narrow land yards through Verticulture was increasing, cheap, applicable and based on local resources.